2007
DOI: 10.1080/09638280600955693
|View full text |Cite
|
Sign up to set email alerts
|

Religion and disability: Clinical, research and training considerations for rehabilitation professionals

Abstract: Religion and spirituality are important coping strategies for persons with disabilities. Practical suggestions for rehabilitation professionals are provided regarding: (a) strategies to enhance religious coping; (b) methods to train rehabilitation professionals about religious issues; and (c) issues to consider regarding future research on rehabilitation and religion.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
41
1

Year Published

2008
2008
2020
2020

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 80 publications
(43 citation statements)
references
References 58 publications
1
41
1
Order By: Relevance
“…Corrigan and Ralph (2005) describe the role of spirituality, in the context of recovery from severe mental illness, as "looking beyond the exigencies of the immediate world for inspiration and guidance" (p. 6). It is likely to be inadequate, however, that the implications of RS in the context of other specific disabilities (Baldwin et al, 2015;Johnstone, Glass, & Oliver, 2007)-such as physical, intellectual, and developmental disabilities-are stated.…”
Section: Introductionmentioning
confidence: 99%
“…Corrigan and Ralph (2005) describe the role of spirituality, in the context of recovery from severe mental illness, as "looking beyond the exigencies of the immediate world for inspiration and guidance" (p. 6). It is likely to be inadequate, however, that the implications of RS in the context of other specific disabilities (Baldwin et al, 2015;Johnstone, Glass, & Oliver, 2007)-such as physical, intellectual, and developmental disabilities-are stated.…”
Section: Introductionmentioning
confidence: 99%
“…12 There are two types of coping strategies to physical and psychological adjustment in patients with disabilities including religious and spiritual approaches. 13 Religiosity is a comprehensive sociological term used to refer to the numerous aspects of religious activity, dedication and belief (religious doctrine), 14 whereas spirituality is defined as subjective and individualistic experiences and helping one understand and find purpose and meaning in life. Indeed, religiosity and spirituality are considered to be central issues in the process of coping with stressors, especially in patients dealing with chronic illness.…”
Section: Introductionmentioning
confidence: 99%
“…Religion has been deemed an important construct in assisting the coping process for many people facing infirmity and affliction [14]. As a result, professionals have become progressively interested in the religion, health, and the quality of life of diverse populations, especially individuals with chronic disabilities [15,16]. For example, Ellison [17] affirmed that a connection with God can produce a level of comfort and a pragmatic awareness of one's purpose and quality of life.…”
Section: Religion and Disabilitymentioning
confidence: 99%
“…Religion can help individuals with disabilities cope, find meaning in their newly constructed reality, achieve contentment and create new goals [15,16,18]. Pragament and Brant [19] showed that religion can produce either successful or unsuccessful mechanisms of coping, depending on the situation and the individual.…”
Section: Religion and Disabilitymentioning
confidence: 99%